2015
DOI: 10.1177/0049475515617571
|View full text |Cite
|
Sign up to set email alerts
|

A clinical evaluation of efficacy and safety of cefepime monotherapy versus piperacillin-tazobactam in patients of paediatric age group with febrile neutropenia in a tertiary care centre of north India

Abstract: We conclude that cefepime monotherapy and piperacillin-tazobactam are equally efficacious and safe in treating patients with febrile neutropenia. Empirical monotherapy with cefepime would prevent an unnecessary extra economic burden as well as avoiding the serious adverse or toxic effects of multi-drug regimes, especially in low- and middle-income countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 18 publications
0
14
0
4
Order By: Relevance
“…Cefepime was compared to several other antibiotics, including ceftazidime ( 13 15 , 17 , 20 ), piperacillin/tazobactam ( 19 , 21 24 ), doripenem ( 25 , 26 ), meropenem, cefotaxime ( 27 ), cefozopran ( 28 ), and ceftriaxone-amikacin ( 16 ). Nearly all of the studies had IV as the route of administration with the exception of Aamir et al, which permitted both IV/IM ( 21 ). The dosage, frequency, and duration of both intervention and comparator antibiotics varied throughout the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cefepime was compared to several other antibiotics, including ceftazidime ( 13 15 , 17 , 20 ), piperacillin/tazobactam ( 19 , 21 24 ), doripenem ( 25 , 26 ), meropenem, cefotaxime ( 27 ), cefozopran ( 28 ), and ceftriaxone-amikacin ( 16 ). Nearly all of the studies had IV as the route of administration with the exception of Aamir et al, which permitted both IV/IM ( 21 ). The dosage, frequency, and duration of both intervention and comparator antibiotics varied throughout the studies.…”
Section: Resultsmentioning
confidence: 99%
“…In four studies, random sequence generation was used in randomization ( 13 , 20 , 21 , 28 ). Aamir et al made use of a computer generated random number for randomization ( 21 ). The study by Kebudi 2001 only reported that “randomization was made using random numbers” ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…The review process is presented in Figure 1 . In brief, from the 2847 studies identified through our search, 30 trials fulfilled our inclusion criteria [ 11 , 12 , 19–46 ]. Furthermore, our screening of article references, review articles, and FDA records yielded 2 additional trials [ 47 , 48 ], as well as supplementary data from a previously identified study [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, trials that used high-dose (2 grams/8 hours, 50 mg/kg per 8 hours) regimens were not associated with increased mortality in the cefepime arm (RR = 1.387; 95% CI, 0.958–2.008; P = .083 and RR = 1.425; 95% CI, 0.979–2.075; P = .064 for all trials and monotherapy, respectively; 10 trials, 1720 patients) [ 19 , 21–23 , 28 , 34 , 40 , 45 , 47 , 48 ]. It is notable that only 1 study [ 28 ] examined combination therapy, whereas the rest were monotherapy trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation